trigonometry math Questions and Answers

Start Your Free Trial

Evaluate the trigonometric sum sin(pi/3)+sin(2pi/3)+sin(3pi/3)+sin(4pi/3) .

Expert Answers info

Inna Shpiro eNotes educator | Certified Educator

calendarEducator since 2013

write619 answers

starTop subjects are Math, Science, and Literature

Since this trigonometric sum involves the angles that are multiples of pi/3 (equivalent to 60 degrees)—a "special" angle with known sine, cosine, and tangent values—each of the terms can be evaluated separately.

  • pi/3 is an acute angle located in the first quadrant, and it has a known sine value: sin(pi/3) = sqrt(3)/2

  • 2pi/3 is located in the second quadrant, so its sine value is positive and equal to that of pi/3: sin(2pi/3) = sqrt(3)/2

  • 3pi/3 = pi. This is a quadrantal angle, located on the x-axis, so its sine is zero: sin(3pi/3) = 0

  • 4pi/3 is located in the third quadrant, so its sine value is negative and equal to the opposite of that of pi/3: sin(4pi/3) = -sqrt(3)/2

Adding it all together, we get sqrt(3)/2 + sqrt(3)/2 + 0 + (-sqrt(3)/2) = sqrt(3)/2.

The value of the trigonometric sum is sqrt(3)/2.

Please see the linked website for more information about the unit circle.

check Approved by eNotes Editorial

Tushar Chandra eNotes educator | Certified Educator

calendarEducator since 2010

write12,554 answers

starTop subjects are Math, Science, and Business

We have to find the result of sin(pi/3) + sin(2pi/3) + sin(3pi/3)  + sin(4pi/3)

We use sin (pi/3) = (sqrt 3)/2

sin (2*pi/3) = sin (pi - pi/3) = sin (pi/3) = (sqrt 3)/2

sin (3*pi/3) = sin (pi) = 0

sin (4*pi/3) = sin (pi/3 + pi) = -sin (pi/3) = -(sqrt 3)/2

Adding  (sqrt 3)/2 + (sqrt 3)/2 + 0 - (sqrt 3)/2

=> (sqrt 3)/2

The required sum of sin(pi/3) + sin(2pi/3) + sin(3pi/3)  + sin(4pi/3) = (sqrt 3)/2

check Approved by eNotes Editorial



giorgiana1976 | Student

We'll group the 1st and the last terms and the middle terms together.

[sin(pi/3)+sin(4pi/3)]+[sin(2pi/3)+sin(3pi/3)]

Since the function inside brackets are matching, we'll transform them into products.

S=2sin[(pi/3+4pi/3)/2]*cos[(pi/3-4pi/3)/2]+2sin[(2pi/3+3pi/3)/2]*cos[(2pi/3-3pi/3)/2]

S=2sin(5pi/6)*cos(pi/2)+2sin(5pi/6)*cos(pi/6)

But cos(pi/2)=0

S=2sin(5pi/6)*cos(pi/6)

We'll write sin(5pi/6) = sin(6pi/6 - pi/6)

sin(5pi/6)=sin(pi-pi/6)

sin(5pi/6)=sin(pi/6)

S=2sin(pi/6)cos(pi/6)

We'll recognize the double angle identity:

S=sin2*(pi/6)=sin(pi/3)

S=sqrt3/2

The value of trigonometric sum is S=sqrt3/2.